Water quality at Tanjung Bajong Coast, Sebuyau, Sarawak - Noziena Mura, Noel (Universiti Malaysia Sarawak (UNIMAS), 2012)
Coastal water samples were collected from 6 sampling stations in Tanjung Bajong coast, Sebuyau, Sarawak. Temperature, transparency, turbidity, depth, pH, conductivity, dissolved oxygen, and salinity were measured directly in-situ while water samples were collected and analyzed in the laboratory for total suspended solids (TSS), BODs, chlorophyll a, orthophosphate, nitrate, nitrite, and 6 heavy metal concentrations which are nickel (Ni), arsenic (As), lead (Pb), manganese (Mn), zinc (Zn), and copper (Cu). The ranges for the physico-chemical parameters were 29.6 -35.1 °C for temperature, 90.0 295.0 NTU for turbidity, 18.3 -23.8 PSU for salinity, 6.49 -10.38mglL for DO, 0.6 -l.4m for depth, 28.48 -34.611lS for conductivity, 7.50 -7.77 for pH, 10 -13mm for transparency, 247.22 -796.89mglL for TSS, 2.73 -6.70mglL for BODs, 5.07 -10.43mglL for chlorophyll a, 0.02 -0.23mglL for orthophosphate, 0.03 -0.043mglL for nitrate, and 0.013 -0.016mglL for nitrite. The heavy metals (mglL) were 0.007 -0.037 for Zn, 0.0711 0.2862 for Mn while Ni, As, Pb and Cu were under detectable limit. Tanjung Bajong coast can be classified as Class E according to MWQS.